BEHAVIORAL EDUCATION FOR ADOLESCENTS WITH AUTISM SPECTRUM DISORDER IN CAREER GUIDANCE ACTIVITIES BASED ON THE PRINCIPLES OF UNIVERSAL DESIGN FOR LEARNING - Thi Quynh Hoa, Nguyen (HNUE Journal of Science: Journal of Educational Science, 2024)
Universal Design for Learning (UDL) is a teaching design approach that provides all students with equal opportunities to learn in an inclusive environment through flexible methods. This article employs methods such as observation, survey, and interviews to study the behavior and behavioral education of adolescents with Autism Spectrum Disorder (ASD) in vocational training activities, approached through UDL principles, at the Hat Giong Center and S.E.E.D Vocational Training Company in Hanoi. The results show that adolescents with ASD exhibit various behaviors in career orientation activities, including disruption, non-compliance, impulsiveness, inattention, aggression, outbursts, rigidity, and inappropriate sexual behaviors. Behavioral education methods based on the principles of UDL were frequently used and effective, such as: constructing a daily activity schedule with pictures; structuring time according to daily activities and individual tasks during lessons; and using a picture-based communication support system. Based on the research results, the article proposes a process for applying UDL in behavioral education for adolescents with ASD in vocational training activities.